Optimization of the Implementation of PSAK 112 in An Effort to Increase Accountability for the Management and Reporting of Waqaf Assets at the Pondok Pesantren Foundation - Risti Ulfi Hanifah; Ahmad Sahri Romadon; S. Sulistyorini (PT Mattawang Mediatama Solution, 2022)
Implementation of Financial Accounting Standards (SAK) PSAK 112: Accounting for Waqaf, which specifically regulates waqaf, is a positive signal for endowments in the country. Especially institutions that are directly involved in waqaf management. So that the management and presentation of waqaf assets at the Islamic boarding school foundation becomes more structured. PSAK 112 regulates accounting for nadzir organizations and wakif organizations. In an effort to optimize the potential of waqaf assets, the Indonesian Waqaf Board stated the need for good, accountable, planned, structured, and systematic management and reporting of waqaf assets as a form of responsibility for nazhir Islamic boarding school foundations with wakif as the endowment party. The implementation of PSAK 112 is to help waqaf managers from the responsibility for managing and reporting waqaf assets to become important. This study aims to analyze the optimization of the implementation of PSAK 112 in an effort to increase accountability for the management and reporting of waqaf assets at Islamic boarding schools foundations, through two questions, namely how Nadzir's participation in the implementation of PSAK 112, how the effect of increasing accountability for asset management and reporting on the implementation of PSAK 112. This is because the participation of nadzir in managing waqaf assets plays an important role in the development of waqaf assets. The results show that the management of waqaf assets at the RM Islamic boarding school foundation is carried out by combining the records of the value of waqaf assets that are debited with the value of donations in the form of infaq, shadaqah, charity that are debited to the foundation's account in the existing financial statements. There are differences in the recording of financial statements made by foundations with regulations, so that the implementation of PSAK 112 on accountability for management and financial reporting of Islamic boarding schools is not optimal. There are several obstacles related to budget management and the preparation of financial reports which are considered not appropriate, this is due to a lack of knowledge about statements of Islamic financial accounting standards and accounting for Islamic boarding schools. Islamic boarding schools only focus on how to record in the form of income minus expenses and used for the purposes of Islamic boarding schools and the benefit of the people.